2022
DOI: 10.1044/2021_jslhr-21-00458
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Language Input Supports Sentence Diversity in Young Children With Autism Spectrum Disorder

Abstract: Purpose: Sentence diversity is a measure of early language development that has yet to be applied to individuals with autism spectrum disorder (ASD). The primary aim of this study was to identify whether children with ASD show change in sentence diversity over 6 months of treatment with Naturalistic Developmental Behavioral Intervention (NDBI). The secondary aim was to examine possible predictors of changes in children's sentence diversity, including caregiver use of NDBI strategies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…First, our sample size of only 20 parent-child dyads may have been too small to detect facilitative input effects for declaratives, an infrequent structure in naturally-occurring parent-child interaction. In previous studies where associations between use of parent declaratives and later child sentence diversity have been detected, sample sizes have been larger, ranging from 28 to 50 dyads (Clark-Whitney et al, 2022;Hadley et al, 2017b;Rispoli et al, 2018). Second, our desire to code the intersection of responsive and linguistic features at the level of the individual utterance led to using a frequency measure of declaratives in parent input rather than the diversity of noun subjects (Hadley et al, 2017a) or the diversity of subject-verb combinations (Rispoli et al, 2018) in active declarative sentences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, our sample size of only 20 parent-child dyads may have been too small to detect facilitative input effects for declaratives, an infrequent structure in naturally-occurring parent-child interaction. In previous studies where associations between use of parent declaratives and later child sentence diversity have been detected, sample sizes have been larger, ranging from 28 to 50 dyads (Clark-Whitney et al, 2022;Hadley et al, 2017b;Rispoli et al, 2018). Second, our desire to code the intersection of responsive and linguistic features at the level of the individual utterance led to using a frequency measure of declaratives in parent input rather than the diversity of noun subjects (Hadley et al, 2017a) or the diversity of subject-verb combinations (Rispoli et al, 2018) in active declarative sentences.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we recommend retaining diversity measures in future studies of linguistic input and using alternative methods for exploring how responsive and linguistic features of input work together to promote child language outcomes. The recent study by Clark-Whitney et al (2022) provides an example of an alternative approach. Recall they combined ratings of caregiver responsivity over time with the baseline frequency of toy talk sentences (i.e., third person declarative sentences about objects and events in the play environment).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, recommendations to avoid single words (stage 1), use lots of contractions that obscure the boundary between subject and predicate (stage 2), and model isolated words without regard to grammar while also avoiding verbs (stage 3), do not square with existing research examining the properties of linguistic input that predict and support language development in NT and autistic children (e.g. Butler et al, 2023 ; Clark-Whitney et al, 2022 ; Hadley et al, 2018 ; Naigles et al, 2011 ). In fact, it is not obvious how NLA stage-specific recommendations would follow from even the raw material view of delayed echolalia on which NLA is founded.…”
Section: A Critical Examination Of Natural Language Acquisition (Nla)mentioning
confidence: 99%
“…In addition, NDBIs have been shown to support expressive language gains via growth in child imitation and intentional communication (Yoder et al, 2021a), providing support for the idea that directly targeting early social communication skills has downstream effects on other developmental outcomes. Indeed, supporting social engagement may enable children to learn optimally from their environment; recent work found that caregiver language modeling was more strongly associated with children’s sentence diversity when caregivers’ NDBI strategy use increased (Clark-Whitney et al, 2022).…”
mentioning
confidence: 99%